2005
DOI: 10.4095/220618
|View full text |Cite
|
Sign up to set email alerts
|

Gas hydrate concentration estimates from chlorinity, electrical resistivity and seismic velocity

Abstract: Gas hydrate beneath the N. Cascadia continental slope off Vancouver Island occurs as a regional diffuse layer above the BSR and as local high concentrations in large vent or upwelling structures. Regional concentrations of gas hydrate beneath the N. Cascadia continental slope off Vancouver Island have been estimated earlier using multichannel seismic, seafloor electrical, and IODP Leg 146 downhole data. The concentrations of between 15 and 30% of pore saturation in a 100 m thick layer above the BSR are much hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 23 publications
1
23
0
Order By: Relevance
“…The estimated concentrations of between 15% and 30% of pore saturation in a 100 m thick layer above the BSR are much higher than estimated elsewhere, especially the Blake Ridge (Paull et al, 1996) and central Cascadia off Oregon during Leg 204 (Tréhu, Bohrmann, Rack, Torres, et al, 2003). Although both of these other studies involved different sediment environments, a careful reevaluation of the northern Cascadia estimates and their uncertainties was carried out by Riedel et al (2005). They concluded that the data and model uncertainties allowed a wide range of concentrations.…”
Section: Riedel Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…The estimated concentrations of between 15% and 30% of pore saturation in a 100 m thick layer above the BSR are much higher than estimated elsewhere, especially the Blake Ridge (Paull et al, 1996) and central Cascadia off Oregon during Leg 204 (Tréhu, Bohrmann, Rack, Torres, et al, 2003). Although both of these other studies involved different sediment environments, a careful reevaluation of the northern Cascadia estimates and their uncertainties was carried out by Riedel et al (2005). They concluded that the data and model uncertainties allowed a wide range of concentrations.…”
Section: Riedel Et Almentioning
confidence: 99%
“…E. Gas hydrate concentrations from the Jarrad et al (1995) reference with a slightly revised empirical porosity-velocity function. F. Gas hydrate concentrations using the Yuan et al (1996) reference profile for accreted sediments (from Riedel et al, 2005). …”
Section: Post-expedition 311 Outlookmentioning
confidence: 99%
“…Historical work with data from Sites 889/890 has shown that the concentration of gas hydrate in sediments has been estimated by using (1) deviations in interstitial water chlorinities from measured baseline conditions, (2) electrical resistivity measurements by applying Archie's relation, and (3) both seismic-and downhole logging-derived P-and S-wave velocities. But results from Leg 146 left many questions unanswered (Riedel et al, 2005), such as:…”
Section: Site U1327mentioning
confidence: 99%
“…An earlier approach by Ussler and Paull (2001) for interpreting chlorinity data from Leg 146 by using a smooth chlorinity baseline suggested lower gas hydrate concentrations at Sites 889/890 but apparently contradicted other geophysical results using electrical resistivity and seismic velocity. In preparation for Expedition 311, the gas hydrate concentrations along the northern Cascadia margin were recalculated using Leg 146 acoustic/electrical resistivity logs and pore water chlorinity/salinity data (Riedel et al, 2005). New estimates show that the concentrations could alternatively be between 5% and 10% on average of the pore volume from ~130 mbsf to the BSR (~230 mbsf).…”
Section: Introductionmentioning
confidence: 99%
“…An emphasis is taken on the salinity background trend and its influence on the regional gas hydrate concentration estimates. Concentration estimates have been a long-debated topic, especially at Ocean Drilling Program (ODP) Leg 146 Site 889 prior to Expedition 311 (e.g., Hyndman et al, 1999;Riedel et al, 2005), as this location exhibits a strongly decreasing trend in pore water salinity down to bottom-simulating reflector (BSR) depths and remains constant below that level, which is unique compared to all others sites drilled during Expedition 311.…”
Section: Introductionmentioning
confidence: 99%